Frequency of endophytic fungi isolated from Dendrobium crumenatum Sw. (Pigeon orchid) and antimicrobial activity - WIBOWO MANGUNWARDOYO; SUCIATMIH SUCIATMIH; INDRAWATI GANDJAR (Society for Indonesian Biodiversity, 2012)
Mangunwardoyo W, Suciatmih, Gandjar I. 2012. Frequency of endophytic fungi isolated from Dendrobium crumenatum Sw. (Pigeon orchid) and antimicrobial activity. Biodiversitas 13: 34-39. Endophytic microorganisms were found in orchid such as Dendrobium crumenatum Sw. (pigeon orchid), an orchid that sometimes used in traditional medicine. The fungi were isolated from roots, bulbouses, stems, and leaves of D. crumenatum collected from Tanah Baru Housing area, Botanical Garden Bogor, and Herbarium Bogoriense, respectively. Twelve species were identified from 60 samples obtained. Guignardia endophyllicola Okane, Nakagiri, and Ito (anamorph:Phyllosticta capitalensis P. Herm.) were the dominant endophytic mould. Screening of the anti-microorganism activity of the samples revealed that Fusarium nivale (Fr.) Ces. inhibited Candida albicans ATCC 2091 and Candida tropicalis LIPIMC 203. All specimens did not inhibit the growth of Bacillus subtilis ATCC 6633, Escherichia coli ATCC 25022, and Staphylococcus aureus ATCC 25023.